PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PT. INDONESIA POWER UPJP KAMOJANG - Cita Insaniah Muhammad; Santoso Tri Raharjo; Risna Resnawaty (Share : Social Work Journal, 2018)
ABSTRACT The concept of corporate social responsibility has been around for thousands of years. The concept of corporate social responsibility has increasingly developed at the beginning of the industrial revolution which began to focus on the problem of corporate responsibility. The implementation of CSR is considered as an effort to create good companies in the public eye. John Elkinkon through the concept of "3P" (profit, people and planet) as a way for companies to survive by making a positive contribution to society (people) and actively taking part in preserving the environment (planet). Budimantara also explained the type of CSR implementation, namely community relations, community services, and community empowering. This study uses the literature study method as an analytic tool. The data used are primary data from interviews and student data.  ABSTRAK Konsep corporate social responsibility sudah ada sejak ribuan tahun yang lalu. Konsep corporate social responsibility  ini semakin berkembang pada awal masa revolusi industri yang mulai berfokus pada masalah tanggung jawab perusahaan. Pelaksanaan CSR dianggap sebagai upaya untuk menciptakan baik perusahaan dimata publik. John Elkinkon melalui konsep “3P” (profit, people, dan planet) sebagai cara bagi perusahaan ingin bertahan dengan memberikan kontribusi positif kepada masyarakat (people) dan ikut aktif dalam menjaga kelestarian lingkungan (planet). Budimantara juga menjelaskan tipe pelaksanaan CSR yaitu community relations, community services, dan community empowering. Penelitian ini menggunakan metode studi literatur sebagai tools analysist. Data yang digunakan data primer dari wawancara dan data sekuder.